HUBUNGAN DERAJAT KEBIASAAN MEROKOK DENGAN DESATURASI OKSIGEN DAN INTOLERANSI AKTIVITAS PADA DEWASA MUDA - Siti Khadijah; Saleha Salihun; Ririn Andasari; Muhammad Taufiq Nugroho; Annasya Nur Sapriyani (Journal of Innovation Research and Knowledge, 2026)
Abstract: Background: Smoking is a major modifiable risk factor affecting the cardiopulmonary system. Even in young adults, cigarette smoking may impair oxygen transport, reduce functional exercise capacity, and increase fatigue before clinically significant respiratory disease develops. This study aimed to determine the relationship between the degree of smoking habits and oxygen desaturation and activity intolerance among young adults. Methods: This analytical observational study used a cross-sectional design involving 35 young adult smokers aged 20–30 years selected through purposive sampling. Smoking exposure was assessed using the Brinkman Index. Oxygen desaturation was measured as the difference in peripheral oxygen saturation (ΔSpO₂) before and after the Six-Minute Walk Test (6MWT). Activity intolerance was evaluated using the 6MWT walking distance and Borg Rating of Perceived Exertion Scale. Data were analyzed using the Shapiro–Wilk normality test and Spearman's rank correlation test. Results: The mean Brinkman Index was 255.43 ± 133.64. Mean oxygen saturation decreased from 98.00 ± 0.69% to 94.89 ± 1.91% after exercise, with a mean ΔSpO₂ of 3.11 ± 1.32%. Significant correlations were found between the Brinkman Index and ΔSpO₂ (r = 0.950), 6MWT distance (r = −0.970), and Borg score (r = 0.979) (all p < 0.001). Conclusion: A higher degree of smoking was significantly associated with greater oxygen desaturation, reduced functional exercise capacity, and increased perceived fatigue in young adults. These findings support the importance of early screening and preventive physiotherapy interventions to maintain cardiopulmonary function.